Cell Sheets of Co-cultured Endothelial Progenitor Cells and Mesenchymal Stromal Cells Promote Osseointegration in Irradiated Rat Bone - Huan Liu (Nature Portfolio, 2017)
Abstract Irradiated bone has a greater risk of implant failure than nonirradiated bone. The purpose of this study was to investigate the influence of cell sheets composed of co-cultured bone marrow mesenchymal stromal cells (BMSCs) and endothelial progenitor cells (EPCs) on implant osseointegration in irradiated bone. Cell sheets (EPCs, BMSCs or co-cultured EPCs and BMSCs) were wrapped around titanium implants to make cell sheet-implant complexes. The co-cultured group showed the highest osteogenic differentiation potential in vitro, as indicated by the extracellular matrix mineralization and the expression of osteogenesis related genes at both mRNA and protein levels. The co-cultured cells promoted ectopic bone formation as indicated by micro-computed tomography (Micro-CT) and histological analysis. In the irradiated tibias of rats, implants of the co-cultured group showed enhanced osseointegration by Micro-CT evaluation and histological observation. Co-cultured EPCs and BMSCs also up-regulated the expression of osteogenesis related genes in bone fragments in close contact with implants. In conclusion, cell sheets of co-cultured EPCs and BMSCs could promote osseous healing around implants and are potentially useful to improve osseointegration process for patients after radiotherapy.